Evaluasi Potensi Pengobatan Tidak Tepat Pada Pasien Geriatri Rawat Inap di RSUD Arjawinangun Berdasarkan Kriteria Beers 2019 - Haqoiroh Haqoiroh; Ditta Novitasari; Ahmad Qoyyim (An-Najat, 2023)
Indonesia is predicted to be in the top 10 largest geriatric populations in the world by 2050. One of the problems in the treatment of geriatric patients is the potential inappropriate medications (PIMs). The Beers criteria can be used to evaluate the prevalence of PIMs. This study aims to evaluate the potential incidence of inappropriate medication use in inpatient geriatric patients at RSUD Arjawinangun using update Beers criteria 2019 and analyze the relationship between the amount of medication used by geriatric patients and the incidence of PIMs. This kind of research is observational research with descriptive-analytical methods conducted retrospectively using a cross-sectional study design. The results of the study showed that of 42 geriatric patients aged >65 years, PIMs were found in 26 patients (59.09%) with a total of 44 PIMs. The incidence of PIMs, or medications that need to be avoided in general for geriatric patients were found in 54.55% of cases, drugs can still be used but with special attention, namely 43.18%, and drug interactions that must be avoided in geriatric patients. Hypertension drugs such as Amlodipine and the diuretic drug Furosemide are the most widely used, but these drugs have the potential to be inappropriate for use in geriatrics. The incidence of PIMs is correlated with the amount of medication used by geriatric patients, according to the results of the Pearson correlation analysis with a P value <0.001.